2014
DOI: 10.1536/ihj.13-169
|View full text |Cite
|
Sign up to set email alerts
|

Changing Prescription Pattern of Omeprazole Among Patients Receiving Clopidogrel

Abstract: SummaryRecent studies have suggested that omeprazole may reduce the inhibitory effect of clopidogrel on platelet aggregation. The United States Food and Drug Administration (FDA) has issued an update regarding this drug-drug interaction.This study aimed to evaluate the changing prescription pattern of omeprazole in patients taking clopidogrel after the FDA update regarding the clopidogrel-omeprazole interaction.A pharmacy database system was used to identify all prescriptions of clopidogrel alone, clopidogrel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…14) Re-cently, a study indicated significant changes in the prescription pattern for omeprazole after the FDA update by taking off omeprazole from the patient's prescription or, to a lesser extent, replacing it with ranitidine. 15) Consequently, a retrospective cohort study, which included 56,406 participants discharged after first-time MI, demonstrated that PPIs are associated with an increased incidence of cardiovascular death, recurrent MI, or stroke, regardless of clopidogrel use. 16) Furthermore, these risks may extend from patients with coronary artery disease to the general population.…”
mentioning
confidence: 99%
“…14) Re-cently, a study indicated significant changes in the prescription pattern for omeprazole after the FDA update by taking off omeprazole from the patient's prescription or, to a lesser extent, replacing it with ranitidine. 15) Consequently, a retrospective cohort study, which included 56,406 participants discharged after first-time MI, demonstrated that PPIs are associated with an increased incidence of cardiovascular death, recurrent MI, or stroke, regardless of clopidogrel use. 16) Furthermore, these risks may extend from patients with coronary artery disease to the general population.…”
mentioning
confidence: 99%
“…7 Additionally, PPI has been linked to other adverse events in the recent past that comprise the clopidogrel (Plavix) resistance, reduced levels of magnesium, which results in elevated leg spasms risks, seizures, arrhythmias, cardiac birth defects when used by a pregnant woman, osteoporotic fractures from persistent use. 10 Similar findings are reflected in a warning issued by the FDA, indicating that omeprazole a PPI has the potential to minimize the antithrombic effect of clopidogrel when the two are concomitantly consumed to almost half. The study noted a drastic reduction in the number of patients that were undergoing combination therapy with one-third still using the combination therapy even after the FDA Safety warning.…”
Section: Research Articlementioning
confidence: 60%
“…Hypertension and severe coronary stenosis are known risk factors for thrombotic cardiac events. Taken together, these three profiles may help predicting which patient may have a higher risk of adverse outcomes when given clopidogrel together with omeprazole [89][90][91].…”
Section: Discussionmentioning
confidence: 99%